Patrimonio histórico y turismo Cultural de la Ciudad de Latacunga - García Meythaler, Carlos Eduardo (2019)
The main objective of this research is to characterize the contribution of Historical Heritage to Cultural Tourism, as premises for the determination of viable alternatives that allow this interrelation to materialize. For the fulfillment of this purpose, the starting point was the establishment of the conceptual theoretical foundations of the historical heritage and cultural tourism categories, allowing us to affirm that the historical heritage contributes significantly to cultural tourism, as a sustainable tourism development strategy. In the same way, the study included the diagnosis in a representative sample of Latacungueños inhabitants, the level of knowledge they possess about the necessary interrelation between historical heritage and cultural tourism, obtaining as main results, that in the population there is an awareness of the importance and relevance of culture, for development processes, social change and, therefore, for tourism activity; turning cultural tourism into a means of development, welfare and social growth requires the conservation, dissemination and promotion of the historical heritage of the place. Different dissemination strategies must be carried out so that the population can value, enjoy and reinvent from its immediate spheres the material, immaterial and natural heritage, which can be achieved as long as the design of a marketing plan for the positioning of the Casa de los Marqueses Museum in the city, to promote and disseminate the works and representations of historical heritage, which constitutes the proposal of the present investigation. The methodology followed for the development of the project was non-experimental, with a cross-sectional design, the type of correlational descriptive study with the same quantitative approach that allowed the research process and in this way the specific and general hypotheses were verified, resulting in historical heritage having an impact and contributing to the activity of cultural tourism in the city of Latacunga.